City’s parameters influence on transportation servicing of goods - Fiyalko, Nataliya; Galkin, Andrii (Lviv Polytechnic Publishing House, 2015)
Production delivery in the consumption sphere is one of the important trade functions that take place in the commercial companies. Rational management is important in goods distribution processes. Logistics tools are affecting on distribution channel delivery mechanism choice for different regions. The sales channels choice is one of the key decisions for the company. The traditional concept of management is not excusing itself. Logistics activities of transportation servicing for various cities in the current market conditions, research not enough. Paper is aimed to improving existing models and approaches to urban transportation servicing of goods carriage.
Keywords: logistics channel; material flow; transport planning cities; Automobilization level; retail network